Developing Virtual Reality Trauma Training Experiences Using 360-Degree Video: Tutorial - Patel, Devika; Hawkins, Jessica; Chehab, Lara Zena; Martin-Tuite, Patrick; Feler, Joshua; Tan, Amy; Alpers, Benjamin S; Pink, Sophia; Wang, Jerome; Freise, Jonathan; Kim, Phillip; Peabody, Christopher; et al. (JMIR Publications, 2020)
Historically, medical trainees were educated in the hospital on real patients. Over the last decade, there has been a shift to practicing skills through simulations with mannequins or patient actors. Virtual reality (VR), and in particular, the use of 360-degree video and audio (cineVR), is the next-generation advancement in medical simulation that has novel applications to augment clinical skill practice, empathy building, and team training. In this paper, we describe methods to design and develop a cineVR medical education curriculum for trauma care training using real patient care scenarios at an urban, safety-net hospital and Level 1 trauma center. The purpose of this publication is to detail the process of finding a cineVR production partner; choosing the camera perspectives; maintaining patient, provider, and staff privacy; ensuring data security; executing the cineVR production process; and building the curriculum.